Neuronal Actin Dynamics, Spine Density and Neuronal Dendritic Complexity Are Regulated by CAP2 - Kumar, Atul; Paeger, Lars; Kosmas, Kosmas; Kloppenburg, Peter; Noegel, Angelika A.; Peche, Vivek S. (Frontiers in Cellular Neuroscience, 2016)
Actin remodeling is crucial for dendritic spine development, morphology and density. CAP2 is a regulator of actin dynamics through sequestering G-actin and severing F-actin. In a mouse model, ablation of CAP2 leads to cardiovascular defects and delayed wound healing. This report investigates the role of CAP2 in the brain using Cap2gt/gt mice. Dendritic complexity, the number and morphology of dendritic spines were altered in Cap2gt/gt with increased number of excitatory synapse. This was accompanied by increased F-actin content and F-actin accumulation in cultured Cap2gt/gt neurons. Moreover, reduced surface GluA1 was observed in mutant neurons under basal condition and after induction of chemical LTP. Additionally, we show an interaction between CAP2 and n-cofilin, presumably mediated through the C-terminal domain of CAP2 and dependent on cofilin ser3 phosphorylation. In vivo, the consequences of this interaction were altered phosphorylated cofilin levels and formation of cofilin aggregates in the neurons. Thus, our studies identify a novel role of CAP2 in neuronal development and neuronal actin dynamics.